Allodynia and hyperalgesia: review - K. D. Dmytriiev; O. V. Marchuk; K. D. Dmytriiev (Медицина болю, 2018)
The main purpose was to highlight the problem of hyperalgesia and allodynia. Main anatomic structures, which participate in nociception were mentioned in this article, with pathologic and pathophysiologic changes, that can be caused by hyperalgesia and allodynia. Main methods of diagnostics and assessment of mentioned symptoms were represented along with the modern approaches to treatment and prevention.